2006
DOI: 10.1002/mrm.20953
|View full text |Cite
|
Sign up to set email alerts
|

DTI‐based assessment of ischemia‐reperfusion in mouse skeletal muscle

Abstract: Diffusion tensor imaging (DTI) is frequently applied to characterize the microscopic geometrical properties of tissue. To establish whether and how diffusion MRI responds to transient ischemia of skeletal muscle, we studied the effects of ischemia and reperfusion using DTI and T 2 -weighted MRI before and during ischemia and up to 24 hr after reperfusion. Ischemia was induced by 50 min of hindlimb occlusion with or without dorsal flexor stimulation. During ischemia the apparent diffusion coefficient (ADC) tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
97
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 42 publications
8
97
1
Order By: Relevance
“…Recently, DTI has been used to determine the characteristics of normal and abnormal muscles in both humans and animals. [12][13][14][15][16][17][18] In this study, DTI as an imaging tool was used to evaluate human inflammatory myopathies, which to our knowledge has not been reported before.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, DTI has been used to determine the characteristics of normal and abnormal muscles in both humans and animals. [12][13][14][15][16][17][18] In this study, DTI as an imaging tool was used to evaluate human inflammatory myopathies, which to our knowledge has not been reported before.…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the anatomical and/or physiological basis of the second and third DTI eigenvectors and eigenvalues, l 2 and l 3 can be expected to be more sensitive to alterations in the dimensions, the shape and the integrity of the skeletal muscle fibers than the principal eigenvalue l 1 . Indeed, Heemskerk et al (166) have recently obtained evidence that, among the DTI eigenvalues, l 3 shows the largest relative response to muscle injury. Figure 8 depicts the time course of l 1 , l 2 and l 3 in mouse tibialis anterior muscle before, during and after a period of severe ischemic stress.…”
Section: Diffusion Mri Of Fiber Architecture and Myocyte Integritymentioning
confidence: 99%
“…Based on the restriction of water diffusion by cell membranes and other subcellular structures and via measuring the intensity of water diffusion in three orthogonal directions, including the primary (l 1 ), secondary (l 2 ) and tertiary (l 3 ) eigenvalues, DTI allows the mapping of the diffusion characteristic of water molecules of biological tissues in vivo. From the previous studies, DTI has been successfully used to non-invasively investigate the diffusive characteristics and microstructure changes of muscular tissues, such as the diffusive properties of the extraocular muscle, 12 the effect of blood flow obstruction and reperfusion, 13 skeleton muscle injury 14,15 and changes after exercise. 16,17 The results demonstrated that there was a geometric correlation between the eigenvalues and muscle fibre architecture.…”
Section: Introductionmentioning
confidence: 99%